PENGEMBANGAN PERMAINAN (GAME-PLAY) EDUKASI GIZI BERBASIS-KOMPUTER UNTUK MURID SEKOLAH DASAR (DEVELOPMENT OF COMPUTER-BASED NUTRITIONAL EDUCATION GAME-PLAY FOR PRIMARY SCHOOL STUDENTS) - Hermina Hermina; Nurfi Afriansyah (Persagi, 2010)
ABSTRACT Background: Nutrition education in school children is considered to be effective and efficient to touch big segment in population. Objective: To develop a computer-based nutritional education game-play for primary school children. Methods: Focus group interviews (focus groups) were used to obtain insight into participants’ understanding and opinions regarding the healthy eating and physical-activity. Participants consisted of pupils (year 3 to 6) and their teachers in 3 cities in West Java Province: Depok, Bekasi, and Bandung. Two primary schools in each city selected purposively based on the recommendation of Dinas Pendidikan (Education Offices). This study included 2 phases. Phase I was focus groups involved 1 pupil group and 1 teacher group of 8 to 10 participants each. Focus group sessions were noted and summarized into meaningful themes for a developed computer-based nutritional education game-play. Phase II was created and test the game-play. Results: Key concepts of the healthy eating were commonly understood, but specific knowledge was limited, especially related to the recommended dietary allowance and food servings. Game-play is develop to be played and can be understood by students and teachers easily. From the trial game-play input obtained to repair the game. So at the end of the study can be obtained prototype game-play more interesting and can be more accepted by students and teachers. Although not all suggestions for improvements can be accommodated perfectly. Conclusion: The computer-based nutritional education game-play can be cheerfully used by year 1 to 6 of primary school children to enrich their knowledge about how much food should they eat a day based on their body needs. [Penel Gizi Makan 2010, 33(2): 161-172] Keywords: computer-based nutritional education, game-play, primary school children, teachers